Hsp90β is involved in the development of high salt-diet-induced nephropathy via interaction with various signalling proteins. Issue 4 (April 2016) - Yan, Shi-hai; Zhao, Ning-wei; Jiang, Wei-min; Wang, Xin-tong; Zhang, Si-qi; Zhu, Xuan-xuan; Zhang, Chun-bing; Gao, Yan-hong; Gao, Feng; Liu, Fu-ming; Fang, Zhu-yuan
Abstract : A high-salt diet often leads to a local intrarenal increase in renal hypoxia and oxidative stress, which are responsible for an excess production of pathogenic substances. Here, Wistar Kyoto/spontaneous hypertensive (WKY/SHR) rats fed a high-salt diet developed severe proteinuria, resulting from pronounced renal inflammation, fibrosis and tubular epithelial cell apoptosis. All these were mainly non-pressure-related effects. Hsp90β, TGF-β, HIF-1α, TNF-α, IL-6 and MCP-1 were shown to be highly expressed in response to salt loading. Next, we found that Hsp90β might play the key role in non-pressure-related effects of salt loading through a series of cellular signalling events, including the NF-κB, p38 activation and Bcl-2 inactivation. Hsp90β was previously proven to regulate the upstream mediators in multiple cellular signalling cascades through stabilizing and maintaining their activities. In our study, 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG) or Hsp90β knockdown dramatically alleviated the high-salt-diet-induced proteinuria and renal damage without altering blood pressure significantly, when it reversed activations of NF-κB, mTOR and p38 signalling cascades. Meanwhile, Co-IP results demonstrated that Hsp90β could interact with and stabilize TAK1, AMPKα, IKKα/β, HIF-1α and Raptor, whereas Hsp90β inhibition disrupted this process. In addition, Hsp90β inhibition-mediated renal improvements also accompanied the reduction of renal oxidative stress. In conclusion, salt loading indeed exhibited non-pressure-related impacts on proteinuria and renal dysfunction in WKY/SHR rats. Hsp90β inhibition caused the destabilization of upstream mediators in various pathogenic signalling events, thereby effectively ameliorating this nephropathy owing to renal hypoxia and oxidative stress.